Film Growth Based on an Organic Basis for Photovoltaic p-Cells - M.N. Orlova; S.I. Didenko; O.I. Rabinovich; V.A. Kolesnikov; A.V. Desyatov; D.S. Saranin (Журнал нано- та електронної фізики)
The main issue is to determine the allowable concentration of the polymer and the acceptor, allowing to obtain a film having a desired density and at the same time, the thickness, the optimum from the point of view of the diffusion length and the probability of dissociation of the intermediate particles with the formation of free charge carriers. From a comparison of the synthesized samples micrographs it can be concluded that the polymer concentration of 12.5 g/l gives a sufficiently dense and relatively uniform film without substantial amounts of undissolved polymer.